Municipal solid waste biochar-bentonite composite for the removal of antibiotic ciprofloxacin from aqueous media - Ashiq, A; Adassooriya, N.M; Sarkar, B; Rajapaksha, A.U; Vithanage, M (Elsevier, 2019)
This study investigates the adsorption of ciprofloxacin (CPX) onto a municipal solid waste derived biochar (MSW-BC) and a composite material developed by combining the biochar with bentonite clay. A bentonite-MSW slurry was first prepared at 1:5 ratio (w/w), and then pyrolyzed at 450 °C for 30 min. The composite was characterized by scanning electron microscopy (SEM), Powder X-ray diffraction (PXRD) and Fourier transform infrared (FTIR) spectroscopy before and after CPX adsorption. Batch experiments were conducted to assess the effect of pH, reaction time and adsorbate dosage. The SEM images confirmed successful modification of the biochar with bentonite showing plate like structures. The PXRD patterns showed changes in the crystalline lattice of both MSW-BC and the composite before and after CPX adsorption whereas the FTIR spectra indicated merging and widening of specific bands after CPX adsorption. The optimum CPX adsorption was achieved at pH 6, and the maximum adsorption capacity of the composite calculated via isotherm modeling was 190 mg/g, which was about 40% higher than the pristine MSW-BC. The Hill isotherm model along with pseudo-second order and Elovich kinetic models showed the best fit to the adsorption data. The most plausible mechanism for increased adsorption capacity is the increased active sites of the composites for CPX adsorption through induced electrostatic interactions between the functional groups of the composite and CPX molecules. The added reactive surfaces in the composite because of bentonite incorporation, and the intercalation of CPX in the clay interlayers improved the adsorption of CPX by the biochar-bentonite composite compared to the pristine biochar. Thus, MSW-BC-bentonite composites could be considered as a potential material for remediating pharmaceuticals in aqueous media.
Keywords: Water treatment Engineered biochar Emerging contaminants Antibiotics Clay composites